Research of High-Speed FBG Demodulation System for Distributed Dynamic Monitoring of Mechanical Equipment. (17th July 2013) - Li, Zhengying; Xu, Zhiqiang; Tang, Zhihao; Zhao, Meng; Cai, Linjun; Liu, Quan
Abstract : This paper designs and implements the high-speed FBG demodulation system which can demodulate multiple FBG sensors (up to 64 sensors in series per channel) of 4 channels synchronously. The system is based on the method of tunable F-P filter. Both the nonlinear effect and the temperature drift effect of the F-P filter are eliminated by applying the triangular-like drive signal and reference channels. In addition, a high-speed adaptive algorithm for peak-find is designed for the system. The experiment results show that, for the whole system, the stability is 2 pm, the resolution is 1 pm, the linearity is 0.999, the measurement precision is 20 pm, and the demodulation frequency is 4 kHz. Consequently, the system is very suitable for distributed dynamic monitoring of complicated mechanical equipment.